Salinity Stress Enhances the Antioxidant Capacity of Bacillus and Planococcus Species Isolated From Saline Lake Environment - Hassan, Abdelrahim H. A.; Alkhalifah, Dalal Hussien M.; Al Yousef, Sulaiman A.; Beemster, Gerrit T. S.; Mousa, Ahmed S. M.; Hozzein, Wael N.; AbdElgawad, Hamada (Frontiers in Microbiology, 2020)
This study aims at exploiting salinity stress as an innovative, simple and cheap method to enhance the production of antioxidant metabolites and enzymes from bacteria for potential application as functional additives to foods and pharmaceuticals. We investigated the physiological and biochemical responses of four bacterial isolates, which exhibited high tolerance to 20% NaCl (w/v), out of 27 bacterial strains isolated from Aushazia Lake, Qassim region, Saudi Arabia. The phylogenetic analysis of the 16S rRNA genes of these 4 isolates indicated that strains ST1 and ST2 belong to genus Bacillus, while strains ST3 and ST4 belong to genus Planococcus. Salinity stress differentially induced oxidative damage, where strains ST3 and ST4 showed increased lipid peroxidation, lipoxygenase and xanthine oxidase levels. Consequently, high antioxidant contents were produced to control oxidative stress, particularly in ST3 and ST4. These two Planococcus strains showed increased glutathione cycle, phenols, flavonoids, antioxidant capacity, catalase and/or superoxide dismutase. Interestingly, the production of glutathione by Planococcus strains was some thousand folds greater than by higher plants. On the other hand, the induction of antioxidants in ST1 and ST2 was restricted to phenols, flavonoids, peroxidase, glutaredoxin and/or superoxide dismutase. The hierarchical analysis also supported strain-specific responses. This is the first report that exploited salinity stress for promoting the production of antioxidants from bacterial isolates, which can be utilized as postbiotics for promising applications in foods and pharmaceuticals.